To simplify the expression 2(3x+4)−3(2x−2)+8(x−5), we can distribute the coefficients to the terms inside the parentheses.
2(3x+4) = 6x + 8
-3(2x−2) = -6x + 6
8(x−5) = 8x - 40
Now, we can combine like terms:
6x + 8 - 6x + 6 + 8x - 40
Combine the x terms: 6x - 6x + 8x = 8x
Combine the constant terms: 8 + 6 - 40 = -26
The simplified expression is 8x - 26. Therefore, the correct answer is 8x−268 x minus 26.
Simplify the expression.
2(3x+4)−3(2x−2)+8(x−5) (1 point)
Responses
20x−2620 x minus 26
8x−388 x minus 38
8x−268 x minus 26
20x+5420 x plus 54
1 answer